Using Artificial Intelligence Technologies in Banks to Achieve Sustainable Performance A Survey Study of Employees of a Sample of Iraqi Banks - Radi, Hasan Hadi Khawo (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
The research seeks to explain the role of the application of artificial intelligence technologies in enhancing sustainable performance in banks, according to its dimensions (economic, social, and environmental), in light of the rapid technological change and the growing need for more sustainable operating models. The research looks at how AI technologies, such as machine learning, big data analysis, worksheet automation, and social media monitoring, can be harnessed to improve the efficiency of banking operations, reduce costs, reduce environmental impact, and enhance banks' social responsibility.The research relied on the descriptive-analytical approach to reach its goals, as a questionnaire was used that was distributed to a sample of employees of five Iraqi commercial banks, and their number reached (130) employees, analyzed the sample's responses using the statistical program (SPSS.24), the research reached a set of conclusions, the most important of which is that there is a positive, significant and statistical correlation between the use of artificial intelligence technologies and the achievement of sustainable performance, which reflects the importance of investing in these technologies as a strategic tool to achieve the sustainable development goals in banks. The most important recommendations are the need for banks to increase investment in artificial intelligence technologies, integrate them with their strategic policies, and develop their human competencies on a continuous basis to ensure the optimal use of these technologies.